Leveraging Digital Transformation for Sustainable Competitive Advantage in Emerging Markets: A Managerial Perspective - Suharyadi, Dedi; Adhi, Sukmono Bayu; Isroni; Irawan, Roy (SAFE-Network, 2025)
Digital transformation has emerged as a critical catalyst for achieving competitive advantage in the knowledge-based economy. This study aims to examine the role of managerial capability in driving digital transformation success and its impact on sustainable competitive advantage among firms operating in emerging markets. Employing a quantitative explanatory survey design, data were collected from 150 respondents consisting of mid and senior level managers in the manufacturing, service, and financial sectors across Indonesia, Malaysia, and Vietnam. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) via SmartPLS 4.0. The results reveal that managerial capability significantly influences digital transformation, which in turn positively affects firms’ dynamic capabilities. Moreover, dynamic capabilities were found to mediate the relationship between digital transformation and sustainable competitive advantage. The institutional context also moderates this relationship, suggesting that regulatory and normative support enhances strategic innovation. These findings highlight that the synergy between managerial vision, digital adoption, and organizational adaptability constitutes the foundation of long-term competitiveness in emerging markets. The study enriches digital strategy literature and offers practical implications for managers and policymakers aiming to foster sustainable digital ecosystems.